2019
DOI: 10.1016/j.tmrv.2019.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Aging on Anemia Tolerance, Transfusion Thresholds, and Patient Blood Management

Abstract: Evidence-based patient blood management guidelines commonly recommend restrictive haemoglobin thresholds of 70 to 80g/L for asymptomatic adults. However, most transfusion trials have enrolled adults across a broad age span, with few exclusive to older adults. Our recent meta-analysis of transfusion trials that focussed on older adults paradoxically found lower mortality and fewer cardiac complications when these patients were managed using higher haemoglobin thresholds. We postulate that declining cardiac outp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 51 publications
1
24
0
Order By: Relevance
“…Anemia in the older population is reported to be related to various medical burdens, including increased morbidity and mortality [7]. In particular, anemia is reported to be related to higher cardiovascular events [8,9], frailty [3,10,11], fractures [12], prolonged hospital stays, and unfavorable outcomes [13][14][15]. Robins et al showed that anemia in older population possesses potential morbidity and mortality by affecting tissue oxygen delivery, accompanying the aging process, and eventually leading to multiple major and minor organ dysfunction, affecting both physical and mental functions [16].…”
Section: Introductionmentioning
confidence: 99%
“…Anemia in the older population is reported to be related to various medical burdens, including increased morbidity and mortality [7]. In particular, anemia is reported to be related to higher cardiovascular events [8,9], frailty [3,10,11], fractures [12], prolonged hospital stays, and unfavorable outcomes [13][14][15]. Robins et al showed that anemia in older population possesses potential morbidity and mortality by affecting tissue oxygen delivery, accompanying the aging process, and eventually leading to multiple major and minor organ dysfunction, affecting both physical and mental functions [16].…”
Section: Introductionmentioning
confidence: 99%
“…Anemia in the older population has been reported to be related to various medical burdens, including increased morbidity and mortality [7]. In particular, anemia has been reported to be related to higher cardiovascular events [8,9], frailty [3,10,11], fractures [12], prolonged hospital stay and unfavorable outcomes [13][14][15]. Robins et al, showed that anemia in older population possess potential morbidity and mortality by affecting tissue oxygen delivery, accompany to aging process, and eventually lead multiple major and minor organ dysfunctioning, which include physical and mental function [16].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the recommended transfusion threshold (7 g/dL) in very old patients has been questioned, and data may indicate that this threshold is too low. 70…”
Section: How To Organize Care?mentioning
confidence: 99%